How a Transition‐Metal(II) Chloride Interacts with a Eutectic AlCl3‐Based Ionic Liquid: Insights into the Speciation of the Electrolyte and Electrodeposition of Magnetic Materials. Issue 20 (25th September 2017) - Pulletikurthi, Giridhar; Weidenfeller, Bernd; Borodin, Andriy; Namyslo, Jan C.; Endres, Frank
Abstract: Electrostatic interactions are characteristic of ionic liquids (ILs) and play a pivotal role in determining the formation of species when solutes are dissolved in them. The formation of new species/complexes has been investigated for certain ILs. However, such investigations have not yet focused on eutectic liquids, which are a promising class of ILs. These liquids (or liquid coordination complexes, LCCs) are rather new and are composed of cationic and anionic chloro complexes of metals. To date, these liquids have been employed as electrolytes to deposit metals and as solvents for catalysis. The present study deals with a liquid that is prepared by mixing a 1.2:1 mol ratio of AlCl3 and 1‐butylpyrrolidine. An attempt has been made to understand the interactions of FeCl2 with the organic molecule using spectroscopy. It was found that dissolved Fe(II) species interact mainly with the IL anion and such interactions can lead to changes in the cation of the electrolyte. Furthermore, the viability of depositing thick magnetic films of Fe and Fe–Al has been explored. Abstract : Charged situation : The electrodeposition of magnetic materials from a eutectic electrolyte—a promising class of ionic liquid—composed of 1‐butylpyrrolidine and AlCl3 is reported.